2012
DOI: 10.3402/tellusa.v64i0.11962
|View full text |Cite
|
Sign up to set email alerts
|

Multi-scale variability of winds in the complex topography of southwestern Norway

Abstract: A B S T R A C T Multi-scale variability of winds in the complex terrain of southwestern Norway is investigated using up to 20 yr of observations from nine automatic weather stations and reanalysis data. Significant differences between the large-and local-scale winds are found. These differences are mainly governed by the large-scale topography of Southern Norway. Winds from the southeast and statically stable flow from the northwest are found to be significantly reduced at the ground level due to large-scale w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
2
12
0
Order By: Relevance
“…When compared to the wind direction at Ulriken, which is on average found to be in reasonable agreement with the larger scale flow direction (Jonassen et al, 2012), the wind direction observed at the other AWSs show large deviations towards a more south and south-easterly direction for the south-westerly flow of Case 1. In the south-westerly flow of Case 2 (before 1800 UTC), the deviations are even larger and it is particularly large at Florida.…”
Section: Observationssupporting
confidence: 54%
See 3 more Smart Citations
“…When compared to the wind direction at Ulriken, which is on average found to be in reasonable agreement with the larger scale flow direction (Jonassen et al, 2012), the wind direction observed at the other AWSs show large deviations towards a more south and south-easterly direction for the south-westerly flow of Case 1. In the south-westerly flow of Case 2 (before 1800 UTC), the deviations are even larger and it is particularly large at Florida.…”
Section: Observationssupporting
confidence: 54%
“…Although the studied windstorms are quite typical in terms of wind pattern (see climatology by Jonassen et al, 2012), there do exist cases where strong and gusty winds in south-westerly flow reach down to parts of the centre of Bergen (e.g. Harstveit, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This pattern is even more significant in braided systems, where variations in fluvial dynamics through time may condition changes in the size of the particles mobilized and subsequently deposited in the surrounding areas. On a local scale, wind circulation is very complex especially in irregular topographic areas, which can increase or decrease wind intensity (Jonassen et al, 2012). Previous work on loess deposits observed that local wind systems in valleys can be important in the formation of aeolian deposits (Sun and Liu, 2000).…”
Section: Site-specific Controls On Sedimentological Processesmentioning
confidence: 99%